Herbicides with the potential to replace paraquat in pre-sowing management of sorghum - Diniz, Jean Carlos Eliazar; Côrrea, Fernando Rezende; Silva, Nelmício Furtado da; Cavalcante, Wendson Soares da Silva; Ribeiro, Daniele Ferreira; Rodrigues, Estevão (Brazilian Journal of Science, 2023)
With the ban on the use of the herbicide Paraquat in Brazil, a test was carried out on possible herbicide molecules that could replace it in the management of desiccation of agricultural areas in pre-sowing of the sorghum crop. The experiment was carried out in the experimental area of the Teaching and Research Farm of the UniBRAS Faculty, in the rural area of the municipality of Rio Verde - GO. An experimental design was used in randomized blocks in a 9 X 3 factorial scheme, with four replications, consisting of nine treatments and three application times. Weed control evaluations were carried out on the sowing day, the biometric and physiological evaluations of the sorghum crop were carried out 35 days after sowing and the data were submitted to analysis of variance which, when significant by the T test, were analyzed by the test of separation of means by Tukey at 5% probability, using the SISVAR® statistical software. The associated use of Glufosinate with Glyphosate, Glufosinate applied alone, Carfentrazone with Glyphosate and the association of Saffufenacil with Glyphosate, promoted greater weed control, as well as better biometric and physiological development of the crop, the treatments did not cause phytotoxicity effect, allowing flexibility in desiccation even in a plant-applied system.